Implementasi Sistem Remunerasi Dan Motivasi Ekstrinsik Terhadap Semangat Kerja Karyawan Pada PT Sinar Sosro KP Sukabumi - Naufal Agung Ferdiana; Erry Sunarya; Resa Nurmala (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Based on the results of observations it was found that employee morale has decreased as seen from employee absentee level data, the average employee absentee level in 2022 is 0.57% or less than 1%. This study aims to calculate and describe the effect of the variable remuneration system and extrinsic motivation on the morale of the employees of PT Sinar Sosro Sukabumi Sales Office. The method used in this research is descriptive and associative research with a quantitative approach. The sampling technique in this study used a non-probability sampling technique or saturated samples. The samples taken in this study were 53 employees. The analysis technique used is multiple correlation analysis, multiple linear regression analysis, coefficient of determination test and partial hypothesis testing (t test) and simultaneously using the F test. The results of the research based on the results of the t test of 3,007 indicate that the remuneration system variable has a significant positive effect on employee morale, while the extrinsic motivation variable has a significant positive effect on employee performance variables with a result of 3,970. Based on the results of the F test of 12,430, it shows that the variable remuneration system and extrinsic motivation simultaneously have a significant influence on employee morale. Keywords: Remuneration System, Extrinsic Motivation, Employee Morale